(untitled) (Orfeu, 2026)
This article aims to catalog musical works for clarinet (and similar instruments) soloist and orchestra written by Brazilian composers. The methodology used was documentary research, involving composer’s catalogs, concert programs, and recordings available online, as well as bibliographic research on works whose theme was Brazilian concert music for clarinet. As a result, a catalog was compiled with 62 works for clarinet and orchestra written by Brazilian composers over a period of approximately 70 years. In addition, it was possible to analyze the historical context and general characteristics of Brazilian music composed for this formation, highlighting the use of two distinct compositional approaches that structure the development of the instrument’s repertoire: one of a nationalist nature, with the insertion of elements of popular culture, and the other based on the aesthetic foundations of contemporary European music.